Better soon than never: climate change induces strong phenological reassembly in the flowering of a Mediterranean shrub community - Pareja-Bonilla, Daniel; Arista, Montserrat; Morellato, Leonor Patrícia Cerdeira [UNESP]; Ortiz, Pedro Luis (Oxford University Press (OUP), 2025)
• Background and Aims Flowering is a key process in the life cycle of a plant. Climate change is shifting flowering phenologies in the Northern Hemisphere, but studies with long data series at the community level are scarce, especially those considering the consequences of phenological changes for emerging ecological interactions. In the Mediterranean region, the effects of climate change are stronger than the global average and there is an urgent need to understand how biodiversity will be affected in this area. • Methods In this study, we investigated how the entire flowering phenology of a community comprising 51 perennial species from the south of the Iberian Peninsula changed from the decade of the 1980s to the 2020s. Furthermore, we have analysed the consequences of these changes for flowering order and co-flowering patterns. • Key Results We have found that the flowering phenology of the community has advanced by ~20 days, which is coherent with the increasing temperatures related to climate change. Individual species have generally advanced their entire flowering phenology (start and end) and increased their flowering duration. The early flowering has resulted in a re-organization of the flowering order of the community and generated new co-flowering assemblages of species, with a slight trend towards an increase of shared flowering time among species. • Conclusions The advanced flowering phenology and changes in flowering duration reported here were of unprecedented magnitude, showcasing the extreme effects of climate change on Mediterranean ecosystems. Furthermore, the effects were not similar among species, which could be attributed to differences in sensitivities of environmental cues for flowering. One consequence of these changes in flowering times is ecological mismatches, indicated by changes in the flowering order and co-flowering between decades. This new scenario might lead to new competitive or facilitative interactions and to the loss or gain of pollinators.
Keywords: climate change; co-flowering patterns; ecological mismatching; emerging ecological interactions; flowering order; flowering phenology; long-term phenology; Mediterranean shrub community; phenological reassembly; temperature rise